Gambaran Karakteristik Pasien Anak dengan Epilepsi di RSUP Prof. Dr. R. D. Kandou Manado - Zafira, Astrid; Salendu, Praevilia M.; Tatura, Suryadi N. N. (e-CliniC, 2026)
Abstract: Epilepsy is a neurological disorder with a high incidence rate in children, characterized by recurrent seizures due to abnormal electric activity in the brain, which disrupts brain function and affects children's mental health, thinking abilities, and social interactions. This study aimed to determine the characteristics of pediatric patients with epilepsy in the Department of Pediatrics, Prof. Dr. R. D. Kandou General Hospital, Manado. This was a retrospective and descriptive study with a cross-sectional approach based on the medical records of pediatric patients aged 1–17 years during the periods of 2023–2024. The variables studied included age, gender, seizure type, EEG results, and the administered antiepileptic therapy. The results showed that out of 60 pediatric patients with epilepsy, there was an increase in cases from 24 patients (2023) to 36 patients (2024), with the largest age group being 1–4 years (48.3%) and the majority being male (58.3%). The most common type of seizure was focal seizures (73.3%), and abnormal EEG results were found in 93.3% of patients. Most patients received monotherapy (78.3%), mainly valproic acid (58.3%), while the most common combination in polytherapy was valproic acid and levetiracetam (8.3%). In conclusion, epilepsy in children at Prof. Dr. R. D. Kandou General Hospital in Manado was most commonly found in males aged 1–4 years with focal seizures, abnormal EEG results, and the most common therapy being valproic acid. Keywords: epilepsy; children; therapies for epilepsy Abstrak: Epilepsi merupakan gangguan neurologis dengan angka kejadian yang tinggi pada anak, ditandai dengan kejang berulang akibat aktivitas listrik di otak yang abnormal, sehingga mengganggu fungsi otak dan berdampak pada kesehatan mental, kemampuan berpikir, serta interaksi sosial anak. Penelitian ini bertujuan untuk mengetahui gambaran karakteristik pasien anak dengan epilepsi di Bagian Ilmu Kesehatan Anak RSUP Prof. Dr. R. D. Kandou Manado. Penelitian ini menggunakan metode deskriptif retrospektif dengan desain potong lintang berdasarkan data rekam medik pasien anak usia 1–17 tahun selama periode 2023–2024. Variabel penelitian meliputi usia, jenis kelamin, jenis kejang, hasil EEG, dan terapi antiepilepsi yang diberikan. Hasil penelitian memperlihatkan dari 60 pasien anak dengan epilepsi, terjadi peningkatan kasus dari 24 pasien (2023) menjadi 36 pasien (2024), dengan kelompok usia terbanyak 1–4 tahun (48,3%) dan mayoritas berjenis kelamin laki-laki (58,3%). Jenis kejang terbanyak ialah kejang fokal (73,3%) dan hasil EEG abnormal ditemukan pada 93,3% pasien. Sebagian besar pasien menerima monoterapi (78,3%), terutama asam valproat (58,3%), sedangkan kombinasi terbanyak pada politerapi ialah asam valproat dan levetirasetam (8,3%). Simpulan penelitian ini ialah epilepsi pada anak di RSUP Prof. Dr. R. D. Kandou Manado paling sering ditemukan pada laki-laki usia 1–4 tahun dengan kejang fokal, hasil EEG abnormal, dan mendapat terapi asam valproat. Kata kunci: epilepsi; anak; terapi untuk epilepsi